Effectiveness of Low-Dose Continuous Gaseous Ozone in Controlling Listeria innocua on Red Delicious Apples During 9-Month Commercial Cold Storage - Shen, Xiaoye; Su, Yuan; Hua, Zi; Sheng, Lina; Mendoza, Manoella; He, Yang; Green, Tonia; Hanrahan, Ines; Blakey, Rob; Zhu, Mei-Jun (Frontiers in Microbiology, 2021)
This study aimed to investigate the effects of low-dose continuous ozone gas in controlling Listeria innocua and quality attributes and disorders of Red Delicious apples during long-term commercial cold storage. Red Delicious apples were inoculated with a three-strain L. innocua cocktail at ∼6.2 log10 CFU/apple, treated with or without 1-methylcyclopropene, and then subjected to controlled atmosphere (CA) storage with or without continuous gaseous ozone in a commercial facility for 36 weeks. Uninoculated Red Delicious apples subjected to the above storage conditions were used for yeast/mold counts and quality attributes evaluation. The 36 weeks of refrigerated air (RA) or CA storage caused ∼2.2 log10 CFU/apple reduction of L. innocua. Ozone gas application caused an additional > 3 log10 CFU/apple reduction of L. innocua compared to RA and CA storage alone. During the 36-week CA storage, low-dose continuous gaseous ozone application significantly retarded the growth of yeast/mold, delayed apple firmness loss, and had no negative influence on ozone burn, lenticel decay, russet, CO2 damage, superficial scald, and soft scald of Red Delicious apples compared to CA-alone storage. In summary, the application of continuous low-dose gaseous ozone has the potential to control Listeria on Red Delicious apples without negatively influencing apple quality attributes.